TIKTOK AS A MEDIUM FOR MUSICAL ACTIVITIES AND ARTISTIC EXPRESSION IN THE PUBLIC SPACES OF PALEMBANG - Tiya Utami (Journal of Education and Teaching Learning, 2026)
This study aims to describe the utilization of the TikTok social media application in musical activities as a form of artistic expression in the public spaces of Palembang City. The study employed a qualitative approach using a descriptive method and was conducted in the Ampera Bridge area, one of the city's busiest public spaces that is frequently used for artistic activities. The research subjects were musicians who performed musical activities while conducting live streaming through the TikTok application in public spaces. Data were collected through observation, interviews, and documentation, while data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results of the study indicate that TikTok is utilized as a medium for broadcasting musical activities to a wider audience and facilitating interaction between musicians and both physical and digital audiences. TikTok-based musical activities in public spaces can be understood as a form of artistic expression that reflects the creativity, identity, and social experiences of musicians. Therefore, the use of TikTok in musical activities within public spaces expands the scope of artistic expression from physical spaces to digital environments and creates new patterns of interaction between musicians and audiences.